Αβ T‐cell receptors with a central CDR3 cysteine are enriched in CD8αα intraepithelial lymphocytes and their thymic precursors. Issue 6 (3rd May 2018) - Wirasinha, Rushika C; Singh, Mandeep; Archer, Stuart K; Chan, Anna; Harrison, Paul F; Goodnow, Christopher C; Daley, Stephen R
Abstract: The thymus plays a crucial role in immune tolerance by exposing developing T cells (thymocytes) to a myriad of self‐antigens. Strong T‐cell receptor (TCR) engagement induces tolerance in self‐reactive thymocytes by stimulating apoptosis or selection into specialized T‐cell lineages, including intestinal TCRαβ + CD8αα + intraepithelial lymphocytes (IEL). TCR‐intrinsic amino acid motifs that can be used to predict whether a TCR will be strongly self‐reactive remain elusive. Here, a novel TCR sequence alignment approach revealed that T‐cell lineages in C57BL/6 mice had divergent usage of cysteine within two positions of the amino acid at the apex of the complementarity‐determining region 3 (CDR3) of the TCRα or TCRβ chain. Compared to pre‐selection thymocytes, central CDR3 cysteine usage was increased in IEL and Type A IEL precursors (IELp) and markedly decreased in Foxp3 + regulatory T cells (T‐reg) and naïve T cells. These findings reveal a TCR‐intrinsic motif that distinguishes Type A IELp and IEL from T‐reg and naïve T cells. Abstract : Thymocytes that undergo strong T‐cell receptor (TCR) engagement in the thymic cortex are induced to die or differentiate into CD8αα + intestinal intraepithelial lymphocytes (IEL). Using a novel sequence alignment approach, Wirasinha et al . report that the presence of the amino acid cysteine in the antigen‐binding site of the TCR is a molecular signature of T cells in the IEL lineage.